History of the Entry of Islam in the North Sumatra Region - Al Zufri, Al Zufri; Suprayitno; Nursukma Suri (al-Afkar, Journal For Islamic Studies, 2025)
Islam entered North Sumatra through trade routes involving merchants from the Middle East, India, and Persia, as well as traders from the Bedouin, Gujarat, China, and Turkey. North Sumatra, with significant ports such as Barus and Samudera Pasai, became a hub of trade activity and the spread of Islam. Historical evidence shows the emergence of Islamic kingdoms such as the Sultanates of Asahan, Serdang, Deli, Bilah, Langkat, and Kualuh, reflecting the local community's acceptance of Islam. The discovery of ancient tombs in various locations in North Sumatra, including Barus and other areas, indicates substantial influence from Persia, Arabia, and China. Additionally, coins from various dynasties, including the Umayyad, Abbasid, and Pandya, found at the Bongal site in Central Tapanuli, highlight extensive trade relations and North Sumatra's significant role in international trade routes. The Aceh Sultanate played a crucial role in the spread of Islam in North Sumatra, supported by historical records from Marco Polo and Ibn Battuta. The discovered coins, particularly those from the Umayyad Dynasty, feature inscriptions in Kufic script, reflecting the dissemination of Islamic messages through monetary artifacts. Research on these coins provides insight into the early development of Islam in North Sumatra and the role of trade and marriage in its spread.